2017
DOI: 10.1177/1010428317697555
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV sensitizes non–small cell lung cancer cells to gefitinib potentially via regulation of SIRT6

Abstract: Astragaloside IV, the active component of Astragalus membranaceus, exhibits diverse biological roles including the antitumor activity. In this study, we evaluated the chemosensitive role of astragaloside IV in non-small cell lung cancer cells. Cell Counting Kit-8 analysis was performed to determine cell viability. Real-time polymerase chain reaction and western blot were used to measure the messenger RNA and protein expression. Results showed that astragaloside IV treatment could suppress the proliferation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…Some researchers reported that CXCR4 is regulated by Wnt/ β -catenin pathway and key factors in EMT pathway are also regulated by β -catenin related ways. Astragaloside IV, an active component in Astragalus membranaceus, and β -elemene, an active component in Curcuma zedoaria, are reported to attenuate the Wnt/ β -catenin pathway by previous reporters [14, 27]. These results are in accordance with our results that decrease the degradation of the β -catenin rescuing the HCT116 from HQEZ.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Some researchers reported that CXCR4 is regulated by Wnt/ β -catenin pathway and key factors in EMT pathway are also regulated by β -catenin related ways. Astragaloside IV, an active component in Astragalus membranaceus, and β -elemene, an active component in Curcuma zedoaria, are reported to attenuate the Wnt/ β -catenin pathway by previous reporters [14, 27]. These results are in accordance with our results that decrease the degradation of the β -catenin rescuing the HCT116 from HQEZ.…”
Section: Discussionsupporting
confidence: 92%
“…Astragalus membranaceus is a traditional Chinese medicine widely used in cancer therapy. It is thought that Astragalus membranaceus restore the immune functions in cancer patients, and some natural components from Astragalus membranaceus enhanced chemosensitivity or inhibited cancer cells directly [1416]. Astragalus membranaceus also protects patients during chemotherapy against liver damage as well as nervous system damage, especially against platinum-derived toxicity [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of SIRT6 promotes tumor cell growth and is closely correlated with the poor prognosis of ovarian cancer, gastric cancer and glioma ( 20 , 25 , 32 ). In non-small cell lung cancer, SIRT6 can suppress cell proliferation via the inhibition of Twist1, and astragaloside IV can sensitize non-small cell lung cancer cells to gefitinib by upregulating SIRT6 ( 33 , 34 ). However, some studies have reported opposite findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several Chinese herbs have been used for treatment of cancer in ancient China, and Astragalosides belong to one class of these agents (Yan et al, 2017). Compounds from Astragaloside, such as Astragaloside II and IV, have been characterized with broad-spectrum antitumor activities (Cheng et al, 2014; Zhang et al, 2014; Dai et al, 2017; Hu et al, 2017; Jiang et al, 2017; Yan et al, 2017). However, the anti-tumor effect of Astragaloside III, an important constituent of Astragaloside, is largely unknown.…”
Section: Discussionmentioning
confidence: 99%